2013
DOI: 10.1111/acer.12254
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Verbal Development and Drinking Behaviors from Adolescence to Young Adulthood: A Discordant Twin-Pair Analysis

Abstract: Background Studies suggest that better cognitive and verbal abilities in childhood predict earlier experimentation with alcohol and higher levels of drinking in adolescence, whereas poorer ability is related to a higher likelihood of remaining abstinent. Whether individual differences in language development in childhood predict differences in adolescent drinking behaviors has not been studied. Methods To address that question, we compared co-twins from twin pairs discordant for their childhood language deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 53 publications
0
28
1
Order By: Relevance
“…In 1 Finnish twin study, it was found that a low assessment of a twin on different measures of verbal ability in childhood in comparison with the other twin was associated with less frequent drinking and intoxication in adolescence (Latvala et al., 2014). There are similar results in an earlier study from the United States, where low cognitive ability was shown to be associated with being a nondrinker among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In 1 Finnish twin study, it was found that a low assessment of a twin on different measures of verbal ability in childhood in comparison with the other twin was associated with less frequent drinking and intoxication in adolescence (Latvala et al., 2014). There are similar results in an earlier study from the United States, where low cognitive ability was shown to be associated with being a nondrinker among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The Rutgers Alcohol Problem Index (RAPI) and The Malmö‐modified Michigan Alcoholism Screening Test (Mm‐MAST) were administered at waves 4 and 5. The RAPI is a 22‐item self‐screening questionnaire that assesses adolescent problem drinking and related negative consequences . The RAPI includes questions about dependence, withdrawal, blackouts, neglect of responsibilities, shame and/or embarrassment to self or others, and inappropriate behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…The Mm‐MAST is originally a nine‐item self‐report scale of current drinking patterns and problems, designed for use in Nordic countries . The scale used in FinnTwin16 had 2 additional items . Each question has two possible answers: “yes” or “no”; the total number of “yes” answers provides the Mm‐MAST total score.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In young adulthood, the variable for drinking to intoxication had these same four categories, while the categorization of the frequency of any drinking was: (0) Less than once a month or never, (1) Approximately once or twice a month, (2) Once a week, and (3) A couple of times a week or more often. These variables have been used in earlier analyses of drinking behaviors in the Finnish twin cohort data (Dick et al, 2011; Latvala et al, in press; Pagan et al, 2006; Rose et al, 1999; Viken et al, 1999). …”
Section: Methodsmentioning
confidence: 99%